Controversies over the mechanisms underlying the crucial role of the left fronto-parietal areas in the representation of tools - Gainotti, Guido (Frontiers in Psychology, 2013)
Anatomo-clinical and neuroimaging data show that the left fronto-parietal areas play an important role in representing tools. As manipulation is an important source of knowledge about tools, it has been assumed that motor activity explains the link between tool knowledge and the left fronto-parietal areas. However, controversies exist over the exact mechanisms underlying this relationship. According to a strong version of the ‘embodied cognition theory’, activation of a tool concept necessarily involves re-enactment of the corresponding kind of action. Impairment of the ability to use tools should, therefore, lead to impairment of tool knowledge. Both the ‘domains of knowledge hypothesis’ and the ‘sensory-motor model of conceptual knowledge’ refute the strong version of the ‘embodied cognition hypothesis’ but acknowledge that manipulation and other action schemata play an important role in our knowledge of tools. The basic difference between these two models is that the former is based on an innatist model and the latter holds that the brain’s organization of categories is experience dependent. Data supporting and arguing against each of these models are briefly reviewed. In particular, the following lines of research, which argue against the innate nature of the brain’s categorical organization, are discussed: (1) the observation that in patients with category-specific disorders the semantic impairment does not respect the boundaries between biological entities and artefact items; (2) data showing that experience-driven neuroplasticity in musicians is not confined to alterations of perceptual and motor maps but also leads to the establishment of higher-level semantic representations for musical instruments; (3) results of experiments using previously unfamiliar materials showing that the history of our sensory-motor experience with an object significantly affects its neural representation.